IMPLEMENTASI ALGORITMA FLOYD WARSHALL PADA APLIKASI PENGADUAN MASYARAKAT BERBASIS ANDROID - Regita Novianti; Rio Andriyat Krisdiawan (NUANSA INFORMATIKA, 2019)
Public complaints are complaints from the public, Government Agencies or other parties verbally or in writing containing information, complaints, dissatisfaction or irregularities in the performance of the National Police that require further handling and settlement. In conducting complaints, the community usually uses short messages (sms) or telephone so that the community must have a personal contact number of the police member who can be contacted. To make it easier for the public to make complaints, a complaint application is needed to find out the policeman to be contacted. Application that will be developed based on preliminary research that took place at Kuningan Police Station. Mobile-based applications that are needed a lot in searching for police and the location of traffic accidents and providing a description of pastoral events. The application that is created only shows the location of the accident in Kuningan Regency. In finding the nearest route, it will be displayed in the form of maps. The police can choose directions from the details of the complaint, then the system will display the results in the form of a route on maps. In this application there is also a service to find out the location of the community by using GPS technology. And the author uses the Floyd Warshall algorithm to determine the nearest police station and determine the route from the location of the police station to the scene. As well as in storing data in this application the author uses MySQL or phpMyAdmin as a web server in storing event data and police data, notifications and reports concerned with the complaint application. And in the development of this application is based on client-server.Keywords: Floyd Warshall Algorithm, GPS, Kuningan Regency, Mobile, MySQL, Police station, phpMyAdmin, Web Server, Community